Pemanfaatan Alat Peraga Edukatif (APE) Berbasis Ekologi untuk Menstimulasi kemampua Fisik Motoruk Anak Usia 4-5 Tahun - Khunaifi, Agus; Sundari, Rista; Khofifah, Nur (Jurnal Ilmiah POTENSIA, 2026)
This study aims to describe the implementation of ecologically based physical motor skills development activities through the use of used materials as educational play materials (ECD) and the role of teachers in supporting early childhood development. The study used a descriptive qualitative approach at RA Hj. Sri Mursyiarti, with children aged 4–5 years and their classroom teachers as subjects. Data collection was conducted through participatory observation using checklists and assessment scales, semi-structured interviews, and documentation. Data were analyzed using interactive analysis techniques, including data reduction, data presentation, and conclusion drawing.The results indicate that ecologically based motor skills development activities were routinely implemented before core learning and were structured using used materials as ECD. These activities were effective in stimulating the development of gross and fine motor skills, coordination, balance, concentration, and self-confidence in children. Furthermore, these activities instilled environmental values ​​through direct learning experiences. The teacher's role was crucial in planning, implementing, and supporting these activities, despite variations in motor skills among children. The conclusions of this study indicate that ecologically based physical motor skills development is an effective, contextual, and sustainable learning strategy in early childhood education.